Minimally Invasive Transforaminal Lumbar Interbody Fusion for Spondylolisthesis and Degenerative Spondylosis: 5-year Results - Park, Yung (Springer US, 2013)
BACKGROUND: Multiple studies have reported favorable short-term results after treatment of spondylolisthesis and other degenerative lumbar diseases with minimally invasive transforaminal lumbar interbody fusion. However, to our knowledge, results at a minimum of 5 years have not been reported. QUESTIONS/PURPOSES: We determined (1) changes to the Oswestry Disability Index, (2) frequency of radiographic fusion, (3) complications and reoperations, and (4) the learning curve associated with minimally invasive transforaminal lumbar interbody fusion at minimum 5-year followup. METHODS: We reviewed our first 124 patients who underwent minimally invasive transforaminal lumbar interbody fusion to treat low-grade spondylolisthesis and degenerative lumbar diseases and did not need a major deformity correction. This represented 63% (124 of 198) of the transforaminal lumbar interbody fusion procedures we performed for those indications during the study period (2003–2007). Eighty-three (67%) patients had complete 5-year followup. Plain radiographs and CT scans were evaluated by two reviewers. Trends of surgical time, blood loss, and hospital stay over time were examined by logarithmic curve fit-regression analysis to evaluate the learning curve. RESULTS: At 5 years, mean Oswestry Disability Index improved from 60 points preoperatively to 24 points and 79 of 83 patients (95%) had improvement of greater than 10 points. At 5 years, 67 of 83 (81%) achieved radiographic fusion, including 64 of 72 patients (89%) who had single-level surgery. Perioperative complications occurred in 11 of 124 patients (9%), and another surgical procedure was performed in eight of 124 patients (6.5%) involving the index level and seven of 124 patients (5.6%) at adjacent levels. There were slowly decreasing trends of surgical time and hospital stay only in single-level surgery and almost no change in intraoperative blood loss over time, suggesting a challenging learning curve. CONCLUSIONS: Oswestry Disability Index scores improved for patients with spondylolisthesis and degenerative lumbar diseases treated with minimally invasive transforaminal lumbar interbody fusion at minimum 5-year followup. We suggest this procedure is reasonable for properly selected patients with these indications; however, traditional approaches should still be performed for patients with high-grade spondylolisthesis, patients with a severely collapsed disc space and no motion seen on the dynamic radiographs, patients who need multilevel decompression and arthrodesis, and patients with kyphoscoliosis needing correction. LEVEL OF EVIDENCE: Level IV, therapeutic study. See the Instructions for Authors for a complete description of levels of evidence.